Mathematics Course Design Based On Six Questions Cognitive Theory Using Hawgent Dynamic Mathematic Software - Liu CunHua; Zhou Ying; Ouyang Qunzhuang; Tommy Tanu Wijaya (Journal on Education, 2019)
In the context of "Internet +", using information and intelligence in the education field has become an inevitable trend now. Based on Six-Questions cognitive theory, taking monotonic functions as an example, designing a mathematic learning media using hawgent to solve problems such as “boredom” and “basic understanding” in they present teaching. The goal is to explore the information technology as it can be a reference to optimizing the classroom teaching.